2020
DOI: 10.1136/bmjopen-2020-039091
|View full text |Cite
|
Sign up to set email alerts
|

Do sex differences in the prevalence of ECG abnormalities vary across ethnic groups living in the Netherlands? A cross-sectional analysis of the population-based HELIUS study

Abstract: ObjectivesMajor ECG abnormalities have been associated with increased risk of cardiovascular disease (CVD) burden in asymptomatic populations. However, sex differences in occurrence of major ECG abnormalities have been poorly studied, particularly across ethnic groups. The objectives were to investigate (1) sex differences in the prevalence of major and, as a secondary outcome, minor ECG abnormalities, (2) whether patterns of sex differences varied across ethnic groups, by age and (3) to what extent convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…In contrast to previous limited evidence on other CVD outcomes [10,11], we observed that sex differences in OHCA incidence are consistent across most ethnic groups, independently of SES. Only in the Moroccan group, the OHCA incidence is more similar between men and women, which is mainly due to the lower OHCA incidence among Moroccan men compared to other men.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous limited evidence on other CVD outcomes [10,11], we observed that sex differences in OHCA incidence are consistent across most ethnic groups, independently of SES. Only in the Moroccan group, the OHCA incidence is more similar between men and women, which is mainly due to the lower OHCA incidence among Moroccan men compared to other men.…”
Section: Discussioncontrasting
confidence: 99%
“…The incidence of OHCA in men and women may differ across subgroups within the population, such as ethnic or socioeconomic (SES) groups. For instance, studies on other relevant cardiovascular disease (CVD) outcomes (e.g., coronary heart disease mortality [10] and major electrocardiographic abnormalities [11]) suggest that sex differences in occurrence of CVD outcomes may be smaller in ethnic minority groups compared to the majority population (in high-income countries), independently of established CVD risk factors. The explanations remain unclear, but may be related to modifying effects of less conventional and potentially overlooked risk factors, such as psychosocial factors (e.g., discrimination) [12].…”
Section: Introductionmentioning
confidence: 99%
“…ECG abnormalities were the main reason for consultation in men at all ages. The higher incidence of ECG abnormalities in men compared with women has been described previously ( 37 , 38 ), and may be partly explained by the higher incidence of cardiovascular disease in men, particularly ischaemic heart disease, which occurs at a younger age ( 39 ). The reason for the higher referral rate may be that general practitioners may be more concerned about the presence of structural heart disease in men with ECG abnormalities.…”
Section: Discussionmentioning
confidence: 64%
“…Our study showed that being male had a positive association with ECG abnormalities. Generally, males are observed to have higher cardiovascular risk at a relatively younger age (37) compared to female counterparts exposed to cardioprotective endogenous estrogen during the fertile period. However, the benefit is lost post-menopausal (38).…”
Section: Discussionmentioning
confidence: 99%